Traffic Management Analysis and Mitigation of Counter-Flow Violations Using Traffic Conflict Techniques in Alam Sutera, Tangerang - Reza Doris Perdana; Sutanto Soehodho; Martha Leni Siregar (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2026)
Wrong-Way Driving (WWD) by motorcycle riders is a critical safety issue in urban Indonesia, with the Alam Sutera area, Tangerang, recording 1,126 violators in a single peak‑hour observation. This study formulates an integrated traffic management and mitigation strategy for the phenomenon of Wrong-Way Driving (WWD) in the Alam Sutera area. The primary issue is driven by the inefficiency of the legal route (1,800 m) compared to the WWD route (270.1 m), which creates a justification for speculative behavior. Proactive safety analysis using the Swedish Traffic Conflict Technique (TCT) identified an extreme fatality risk with an average Time-to-Accident (TA) value of 0.7 seconds, with 80% of interactions categorized as serious conflicts. Questionnaire analysis based on the Theory of Planned Behavior (TPB) confirmed a critical detour distance threshold at >1,000 m, which serves as a trigger point for driving violations. Evaluation through VISSIM microsimulation (validated with GEH value <  5 and MAPE value < 50% ) shows that Scenario 3 is the most optimal mitigation. By implementing a 1.20 km alternative route via the roundabout, installing permanent physical barriers, and optimizing the traffic signal cycle time from 143 seconds to 90 seconds, the traffic volume load at the conflict point was significantly redistributed. This strategy effectively enhancing operational performance by reducing average delay to 20.34 seconds/vehicle at Level of Service (LOS) C.